Inovação e desenvolvimento : estudo de caso da Sergipe Administradora de Cartões e Serviços S/A - Silva, Rafael Santos da (2022)
Micro and small companies (SMEs) were affected by the evolution of the credit card market, especially after law 12.865/2013, which was established to standardize and regulate the market of means of payments that are part of the SPB (Brazilian Payment System). Fact this, which was a milestone in the credit card market, which in turn impacted all the agents involved.From this regulation, the market initiated a series of transformations of procedures and availability of technologies. Thus, the present work aims to present a case study of Sergipe Administradora de Cartões e Serviços S/A. (SEAC), based on the theoretical basis the verification how the process of innovation and development contributes and influences to the MEPs, seeking the repercussions of the TKS product on micro and small companies, in particular for those operating in the retail trade in Sergipe during the period between 2014 and 2019. No regarding the methodology, a descriptive research will be carried out, in which will be observed the transformations of the Sergipe SMEs of the retail trade before the TKS product of SEAC. As for the way of approach to the research, it will have a quantitative and qualitative character. In relation to technical procedures, a bibliographical research will be carried out on the importance of innovation in the competitive process between companies and technological development, in addition to the case study on SEAC. Additionally, secondary data will be collected to characterize the Sergipe SMEs of the retail trade, analyze the evolution of the credit card market. The research revealed that the developments that have occurred in recent years in the credit card market have had considerable impacts on the routines and management of MEPs in Sergipe, such as pricing, cash flow control and the difficulty in negotiating fees charged by card companies.